Environmental restoration with forest trees in the Southern State of Parana grasslands - Sousa, Letícia Penno de (2010)
Human development activities as water reservoir construction have great impact on the vegetation, thus changing its floristic, as well as its structure and ecology functions. Parana Pine Forest alongside with grasslands have been highly modified and in particular to the last one, there are few works related to its restoration. In the border of Irai water reservoir (Metropolitan Region of Curitiba, PR), where occurs grasslands associated to the Parana Pine Forest, where it were establishedtree plantations aiming rescue tree vegetation lost due to the flooding. Inside these plantations, an experiment was established to compare growth and survival of eight local native species in 12 months, in single species plots and under the same environmental conditions. Results for the species Escallonia  montevidensis, Lafoensia pacari, Lithraea molleoides, Luehea divaricata, Mimosa scabrella, Podocarpus lambertii and Vitex megapotamica presented very undesirable attributes, where height ranged between 10 cm and 33 cm, diameter ranged between 2.5 mm a 6.6 mm and survival percentage was between 9.1 and 66. 7 . It was possible to claim these results to water deficit, soil with low base saturation, to delayed plantingand to high plant evapotranspiration. Actions dealing with restoration must consider limits and possibilities concerning each phytoecological region and proper restoration techniques as well.